EVALUATION OF THE EFFECT OF FLAVONOIDS ISOLATED FROM SILYBUM MARIANUM ON LYMPHOCYTES OF ADULT FEMALE RATS AND THEIR FETUSES (MTT ASSAY) - Saleh, Ahmed Hamad (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aimed to evaluate the effects of flavonoids isolated from Silybum marianum (milk thistle) on the lymphocytes of adult female rats and their fetuses, focusing on cytotoxicity and compound characterization. Method: Fresh leaves collected from Sulaymaniyah, Iraq, in January 2025 were subjected to flavonoid extraction and analyzed using High Performance Liquid Chromatography (HPLC) and Fourier Transform Infrared Spectroscopy (FT-IR) to identify phenolic compounds. Lymphocytes were isolated from rat blood samples via density gradient sedimentation, and MTT assays were performed to assess cell viability at different extract concentrations (25, 50, and 100 μg/ml). Results: HPLC analysis identified several flavonoids, with 4-hydroxyl benzoic acid (282.5 ppm) and catechol (233.1 ppm) being the most abundant. Cytotoxicity tests showed high lymphocyte viability for both adult females (92.34–81.35%) and fetuses (91.92–81.7%), with IC₅₀ values of 324.9 μg/ml and 347.3 μg/ml, respectively. Novelty: The study demonstrates that S. marianum leaf extracts are rich in bioactive flavonoids with low cytotoxic effects on lymphocytes, suggesting potential for safe therapeutic use in antioxidant or protective applications.